Deliberation as a Collective Decision-Making Mechanism in Multicultural Communities - Anđelković, Nemanja (HAPSc Policy Briefs Series, 2022)
In this policy brief, the potential that deliberative democracy as a decision-making process has for enhancing the inter-cultural dialogue and dealing with the issues present in multicultural communities is examined. Besides analyzing the advantages of deliberation and its operationalization in reality, in the final part of the policy brief, I offer some possible paths for improving the deliberative process in fostering intercultural communication and problem-solving.